Polymorphisms in the Leptin Receptor (LEPR) Gene and Their Association with Growth and Reproductive Traits in Indonesian Sheep - Rojib; C. Sumantri; A. Gunawan (Tropical Animal Science Journal, 2026)
The leptin receptor (LEPR) gene is a potential gene associated with growth and reproductive traits in livestock. However, studies on local Indonesian sheep are very rarely conducted. This study aimed to investigate the LEPR gene polymorphism and its association with growth and reproductive traits in Indonesian sheep. A total of 553 DNA samples were used to identify LEPR gene polymorphisms in Indonesian sheep populations. The sheep population used was 313 crossbred lambs (Garut × Garut, Dorper × Garut, Batur × Garut, and Suffolk × Garut) observed to determine the association of the LEPR gene with growth traits, while 240 Garut ewes were also examined to determine the association of the LEPR gene with reproductive traits. The genetic variation of sheep breeds was assessed using the PCR-RFLP technique with the restriction enzyme Aci1. The correlation of growth and reproductive Traits associated with Genotypes was assessed using a General Linear Model (GLM). The result indicated that the LEPR gene was polymorphic in Indonesian sheep breeds and produced two alleles (A and C) and three genotypes (AA, AC, and CC) according to the Hardy-Weinberg Equilibrium. The polymorphisms of the LEPR gene were statistically significant in association with the weight of the lamb at birth and the weight of the lamb at weaning (p<0.05). The lambs that were homozygous AC had significantly higher births and weaning weights (p<0.05) than those lambs with the AA genotype. The LEPR polymorphisms were not found to be associated with average litter size or offspring mortality. These findings indicate that the LEPR gene is a promising candidate marker for improving growth performance, particularly birth weight and weaning weight, in Indonesian sheep.